AB1319 Examination of determinants of patient preferences for total knee replacement (TKR) among men and women. (23rd January 2014) - Kwoh, C.K.; Cloonan, Y.; Boudreau, R.; Hannon, M.; Vina, E.; Ibrahim, S.
Abstract : Background: Elective TKR is an effective treatment option for end-stage knee osteoarthritis (OA) that is rapidly growing. Although women have as much or greater prevalence of knee OA than men, men undergo TKR more often than women. Patient preference is emerging as an important consideration in TKR gender disparities. However, few studies have examined the determinants of patients' preference in a racially diverse sample of men and women. Objectives: We sought to identify whether determinants of patients' preference for TKR differ by gender. Methods: Our sample consisted of 509 women (59% white) and 290 men (73% white) with chronic, frequent knee pain and radiographic evidence of knee OA. We used logistic regression models, stratified by gender, to identify clinical and socio-cultural determinants of patients' preference for TKR. Clinical and socio-cultural factors were entered simultaneously into the stratified models. Stepwise selection methods were used to select socio-cultural items to be included in the final models, using a criterion of p<0.20. All models were adjusted for age, income level, disease severity (using the WOMAC), and study site. Results: White women had lower preference for TKR compared to white men (adjusted OR=0.56, 95%CI 0.34 to 0.94), whereas African-American (AA) women had higher preference for TKR compared to AA men (adjusted OR=1.24, 95%CI 0.70 to 2.18). Among women, items related to knowledge (p<0.001) and expectations (p=0.007) regarding surgical outcomes, and religiosity (p=0.045) were selected for inclusion in the multivariate model. Among men, items related to knowledge (p=0.46) and expectations regarding surgical outcomes (p=0.027) were selected for inclusion in the multivariate model (see Table 1 ). Conclusions: Expectations regarding surgical outcomes are important for both men and women with regard to their preferences for TKR, but the genders differ with regard to which other socio-cultural determinants impact these preferences. Interventions to reduce or eliminate gender disparities in the utilization of TKR should consider and target these factors. Disclosure of Interest: None Declared